STUDI KOMPARATIF PEMBELAJARAN MODEL NHT DENGAN MODEL JIGSAW (MEMPERTIMBANGKAN BENTUK SOAL) TERHADAP HASIL BELAJAR IPS. - Didi Sudarmasyah; Nurdin Nurdin; Eddy Purnomo (JEE (Jurnal Edukasi Ekobis), 2013)
The study was backed by low of learning outcomes and the lack ofactivity in social science learning of students in class VIII at SMP N 1 BatangHari East Lampung. The objectives of this research are; students’ social sciencelearning results differences between students who use NHT cooperative learningmodel and those who use Jigsaw cooperative learning model without consideringtheir forms of test (multiple choice and essay). This research uses experimentmethod. Samples were taken using Cluster Random Sampling. Data wereanalyzed using t-test and Two-Way Variant Analysis test.The results showed: (1) there was a mean difference of social science learningoutcomes between students who use cooperative learning model NHT type withstudents who use cooperative learning model Jigsaw; (2) there was a meandifference of social science learning outcomes between students who tested byusing a form of multiple choice questions, and students who tested by using a formof essay questions; (3) there is no interaction between learning model with theform of test; (4) The average of social science students learning outcomes learnedby using cooperative learning model NHT type more high than learned by usingcooperative learning model Jigsaw type if learning outcomes measured by usingmultiple choice questions; (5) The average of social science students learningoutcomes learned by using cooperative learning model NHT type more high thanlearned by using cooperative learning model Jigsaw type if learning outcomesmeasured by using essay questions; (6) The average of social science studentslearning outcomes tested by using a form of multiple choice questions more highthan tested by using a form of essay questions on cooperative learning modelNHT type; (7) The average of social science students learning outcomes tested byusing a form of multiple choice questions more high than tested by using a form ofessay questions on cooperative learning model Jigsaw typeKeywords: learning outcomes, NHT learning, jigsaw learning, form of test.